Strategi Transformatif Nawaning Nusantara dalam Pencegahan Kekerasan Seksual di Pesantren - Sa’dyah, Halimatus (Universitas Al-Qolam Malang, 2025)
Pesantren is an Islamic educational institutions that has existed since before independence. Their image has declined due to several instances of sexual violence within them. While traditionally safe and welcoming institutions for children and women, they have been stigmatized by the actions of certain individuals. The purpose of this study was to determine Nawaning Nusantara's strategy for preventing sexual violence in Islamic boarding schools. This study used a case study with a qualitative approach to data collection and analysis through observation, interviews, and literature review from various written sources in online media. The results revealed that Nawaning Nusantara has a strategic plan, including a sexual violence prevention mitigation agenda, workshops, and training for facilitators for tarbiyah jinsiyah. Efforts to prevent sexual violence in Islamic boarding schools include monitoring within the boarding school, consulting with religious leaders (kyai), official regulations on boundaries between men and women, and studying the yellow book on sexual education and gender understanding through the KGI (Ngaji KGI) study and Qira’ah Mubadalah perspective.